Students' Accounts of Their First-Year Undergraduate Academic Writing Experience: Implications for the Use of the CEFR. Issue 1 (2nd January 2018) - McNamara, Tim; Morton, Janne; Storch, Neomy; Thompson, Celia
ABSTRACT: This article addresses the suitability of the CEFR as the basis for decisions about the readiness of individuals to engage in academic writing tasks in undergraduate university courses, and as a guide to progress. The CEFR offers potentially relevant general scales and subscales, but also more specific subscales for writing in the academic context. However, recent challenges to traditional views of academic writing have potential implications for assessment frameworks such as the CEFR when they are used to identify readiness for, and progress in, academic study. In this article we explore the views of students on what it means to "do" academic writing. Questionnaires, interviews, and short reflective texts were used to investigate the changing perceptions of first-year undergraduate students at an Australian university. The analysis of student data confirms the reality of the more complex view of academic writing suggested by the recent literature. The article then considers what implications this has for the adequacy of the definitions provided in the CEFR. It suggests that the CEFR descriptors underrepresent the complexity of the challenges of academic writing, particularly its cognitive demands. A new and rather different approach will be required to inform assessments used to manage the admission of students in`to academic writing contexts and the monitoring of their progress.